Programa PNAD: uma construção científica - Nogueira, Elizabeth Saramela (2012)
Submitted by Julie_estagiaria Moraes (julie.moraes@fgv.br) on 2012-01-26T14:53:22Z No. of bitstreams: 1 000061158.pdf: 27006837 bytes, checksum: 911b7aa9e43c353575a4a3726852c2e6 (MD5) === Made available in DSpace on 2012-01-26T15:35:30Z (GMT). No. of bitstreams: 1 000061158.pdf: 27006837 bytes, checksum: 911b7aa9e43c353575a4a3726852c2e6 (MD5) Previous issue date: 1993 === Study about the review process of the conceptual and methodological parameters that guide the National Research per Domicile Sampling (PNAD) of the Instituto Brasileiro de Geografia e Estatistica (IBGE) Organization in the period between 1989 and 1992. Its purpose is to show the statistical production process, as well as to understand the relationships that exist among object, theory and method in measurement- oriented surveys. In the ligth of reflections about the building of s cientific knowledge and the role of method in the survey process, the specificity of the statistical method is discussed. The results indicate that PNAD's construction process is affirmed as a scientific act. === Estudo sobre o processo de revisão dos parâmetros conceituais e metodológicos norteadores da Pesquisa Nacional por Amostra de Domicilios - PNAD, da Fundação Instituto Brasileiro de Geografia e Estatistica IBGE, abrangendo o periodo de 1989 a 1992. Objetiva-se mostrar o processo de produção estatistica, bem como compreender as relações entre objeto, teoria e método em investigações voltadas para a mensuração do real. A luz de reflexões sobre a construção do conhecimento cientifico e o papel do método no processo de pesquisa, discute-se a especificidade do método estatistico. Os resultados indicam que o processo de construção da PNAD se afirma como um fazer cientifico.